Evaluation of Bioactive Compounds, Antioxidant, and Anti-Diabetic Activities in Hexane and Supercritical Carbon Dioxide Extracts of Sweet Potato (Ipomoea batatas L.) Leaves - Nasori, Achmad Sofian; Wiguna, Bangkit; Rahayu, Maya Damayanti; Permatasari, Devi; Kazfia, Hananda; Muhamaludin; Rosyidin, Ahmad Khulafaur; Dewi, Rizna Triana; Fu, Minghai; Atmaji, Priyo; Aji, Galih Kusuma (Science and Technology Indonesia, 2025)
Sweet potato leaves are a rich source of bioactive compounds with potential health benefits. Advanced methods are being explored to harness these beneficial compounds efficiently. Applying the supercritical carbon dioxide (SCO2) technique, as an environmentally friendly extraction technique, offers many advantages over traditional solvent extraction. This study, therefore, aimed to investigate the effect of SCO2 extraction on the bioactive properties of sweet potato leaves, focusing on antioxidant and anti-diabetic activities. Then, the SCO2 extracts were compared with the hexane extract. A completely random design was used, performing 3 pressures (2000, 3000, and 4000 Psi) and 3 temperatures (40, 50, and 60°C) for the SCO2 extraction. In addition, a maceration using hexane solvent was performed in a shaker for 24 hours. Total polyphenol and flavonoid concentrations were quantified, and gas chromatography-mass spectrometry (GCMS) analyses were used to identify the extracted bioactive compounds. Antioxidant and anti-diabetic activities were also assessed. This yield of SCO2 extraction ranged from 0.49% to 0.89%, which was significantly lower in yield, polyphenol, flavonoid concentration, and antioxidant activity compared to hexane extract (P<0.05). Despite the lower yield, this study observed a higher concentration of bioactive terpenoids such as phytol, caryophyllene oxide, and squalene. In terms of anti-diabetic activity, the extracts at SCO2-specific conditions (4000 Psi 40°C, 3000 Psi 60°C, 3000 Psi 40°C, and 60°C, 2000 Psi 60°C) exhibited potent alpha-glucosidase inhibition, with IC50 values comparable to acarbose, and hexane extract. Dipeptidyl peptidase 4 (DPP4) inhibition was the highest in the hexane extract (p < 0.05), followed by SCO2 extracts. Thus, these findings highlight new possibilities for developing anti-diabetic agents derived from sweet potato leaves using the green SCO2 extraction technique.